The critical eye : fifteen pictures to understand photography - Rexer, Lyle (Intellect Books Ltd, 2019)
The Critical Eye provides a comprehensive approach to the critical understanding of photography through an in-depth discussion of fifteen photographs and their contexts - historical, generic, biographical and aesthetic. Lyle Rexer argues that by concentrating on just a few carefully chosen works it is possible to understand the history, development and contemporary situation of photography.